2021
DOI: 10.1038/s41390-021-01493-8
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory morbidity in preterm infants predicted by natriuretic peptide (MR-proANP) and endothelin-1 (CT-proET-1)

Abstract: Background Bronchopulmonary dysplasia (BPD) is a major complication in preterm infants <32 weeks. We aimed to assess whether plasma levels of mid-regional pro-atrial natriuretic peptide (MR-proANP) and C-terminal pro-endothelin-1 (CT-proET-1) predict respiratory morbidity. Methods This was a prospective, two-center, observational cohort study. MR-proANP and CT-proET-1 were measured at day 7 (±2) of life. Associations with duration of supplemental oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A recent prospective study of 229 premature infants suggested that the precursors of atrial natriuretic peptide (ANP) levels measured on the 7th day of life (±2 days) were associated with combined outcomes of BPD or death in univariable models but not after adjusting for cofactors ( 53 ). Both ANP and BNP belong to the natriuretic peptide family.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective study of 229 premature infants suggested that the precursors of atrial natriuretic peptide (ANP) levels measured on the 7th day of life (±2 days) were associated with combined outcomes of BPD or death in univariable models but not after adjusting for cofactors ( 53 ). Both ANP and BNP belong to the natriuretic peptide family.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 20 However, the above classic markers are mostly non-specific indicators such as inflammatory factors, making it difficult to distinguish between primary disease and BPD in infants with acute respiratory distress syndrome. 2 Therefore, serum IL-6 and IL-33 21 , 22 as inflammatory cytokines, serum ET-1 and KL-6 23 , 24 as lung injury markers were measured, and compared between BPD and non-BPD infants. And, the four biomarkers did not exhibit continuous changes during the development of BPD ( Figure 4 ), which cannot explain the pathological mechanism of BPD well.…”
Section: Discussionmentioning
confidence: 99%